Pendekatan Komunikatif Terhadap Kemampuan Berbicara Bahasa Arab Siswa Kelas XI MA Al-Islamiyah Bebidas - Anwir; Ulyah Darajah (Jurnal Ilmu Pendidikan, 2025)
Speaking skills (Maharah al-Kalam) are one of the main pillars in learning Arabic as a means of communication and interaction, especially in Madrasah Aliyah. This research is motivated by the importance of finding effective approaches to improve students' verbal skills, and the Communicative Approach is considered to have great potential because it is oriented to the use of language in a real context. This study aims to determine the significance of the influence of the Communicative Approach on improving the Arabic speaking ability of Class XI MA students. Al-Islamiyah Bebidas East Lombok Academic Year 2024/2025. This study uses a quantitative approach with experimental design. Data was obtained through a comparison of the results of the speaking skills of students who were taught using the Communicative Approach with other approaches. The data were analyzed using a t-test to test the research hypothesis. The results of the data analysis showed that there was a significant influence of the application of the Communicative Approach on students' Arabic speaking ability. The results of the statistical test showed that the value was greater than , which was 6.236 > 2.704. Thus, H0 is rejected and Ha is accepted. It can be concluded that the Communicative Approach has a positive and effective influence in improving the Arabic speaking ability of Class XI MA students. Al-Islamiyah Bebidas East Lombok. This approach has been shown to be superior in producing better Arabic speaking skills compared to other teaching approaches.